The build-borrow-or-buy framework - Moreno León, Jorge Francisco (2022)
This academic paper covers the subject of the build-borrow-or-buy framework and its use in international business. The multinational companies use the build-borrow-or-buy framework to know if a company, which has the intend to enter in a foreign market, should apply internal development (build), strategic alliances (borrow) or acquiring an existing company (buy). The content of this document has been extracted from the Strategic Alliances course lessons taught in the International Business career.